An enterprise opportunity for entrepreneurial students: student enterprise development and experience assessed through the student voice. Issue 7 (8th August 2016) - Bell, Robin; Bell, Heather
Abstract : Purpose: This research investigates the effectiveness of an experiential learning approach, available to students in all disciplines that combined a hands-on entrepreneurial and enterprise experience with professional consultant mentoring by using a competition to win business start-up funding. Design/methodology/approach: Students at a UK university had the chance to enter a competition in which they developed an entrepreneurial idea and then designed and presented a business plan to win business start-up capital. Students who were entrepreneurially motivated, but who lacked capital to start up their business, were targeted, as these students have been argued to benefit the most from a combination of business plan training and entrepreneurial development. Feedback and data was obtained from the students at each stage of the process and was thematically analysed to assess the development of students' entrepreneurial skills and knowledge through the experience. Findings: The research found that the benefits gained from this approach included both enterprising and entrepreneurial skills, with the greatest impact being on student confidence and belief in their ability to start a business. The practical skills had a 'demystifying' effect on students that made them feel like entrepreneurship and enterprise start-up were attainable. Research limitations/implications: The research focused on students at one UK University and centered on entrepreneurship in a retail business. The competition thus appealed mainly to students who were interested in retail start-up, thus leaving out some enterprising students whose feedback may have been different. In addition, while entrepreneurial skills are assessed in the data, the students who would be interested in the competition would be assumed to be proactive, and this skill was not able to be analyzed. This research is a single case, and thus could be enhanced by more cases and looking at other enterprise start-up means beyond retail. Originality/value: This research makes a case that, in light of literature critical of the use of business plan training in entrepreneurship education, certain students are appropriate candidates for this approach. Specific skills and knowledge can be developed in university students using a live enterprise experience, supported by entrepreneurial mentoring. By making the event extracurricular, the study sought to capture the feedback of students who self-selected into the program, who can benefit most from combined entrepreneurial and business-plan development experience.